What’s So Special About Medically Assisted Dying? - Sumner, Wayne (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Critics of Canada’s current medical assistance in dying (MAiD) regime commonly employ two types of argument: 1) that the number of annual provisions shows that it is out of control or on a slippery slope, and 2) that it puts persons with disabilities at risk. Both arguments commit the same fundamental mistake: treating MAiD as different in kind from other forms of medical treatment, including end-of-life treatment.